Ocena obremenitve slovenskih vod s hormoni in izbranimi hormonskimi motilci - Grobin, Andrej (Farmacevtski vestnik, 2024)
Hormones and some active pharmaceutical ingredients can act as endocrine disruptors (EDs) in the environment, which can have serious effects on aquatic organisms and humans. Due to insufficient data on their occurrence and risks, we developed and validated an ultra-sensitive analytical method for quantitative determination of the occurrence of 25 different EDs. With it, we analyzed 36 wastewater and 33 river water samples and successfully quantified 16 EDs, with the highest concentrations of bisphenols (BPs) S, A and F, estriol and chlormadinone, and with concentrations above safe levels for estradiol and ethinyl estradiol. We determined that wastewater treatment plants are generally successful in the removal of most EDs but are currently overburdened. The presence of BPA, estradiol, BPS and estrone represents high risk in the majority, and the presence of synthetic steroids in a tenth of the river water samples, with the safe limits exceeded by two orders of magnitude in several samples.
Keywords: čistilne naprave; endocrine disruptors; Hormonski motilci; kemični motilci endokrinega sistema; ocena tveganja; Površinske vode; risk assessment; surface water; wastewater treatment plants